2017
DOI: 10.1007/s10157-017-1458-x
|View full text |Cite
|
Sign up to set email alerts
|

Ratio of blood urea nitrogen to serum creatinine at initiation of dialysis is associated with mortality: a multicenter prospective cohort study

Abstract: The BUN/Cr ratio at the time of initiation of dialysis was associated with all-cause mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 28 publications
0
27
0
1
Order By: Relevance
“…We postulate that the urea-to-creatinine ratio might serve as a biomarker indicative of frailty. Elderly are more susceptible to dehydration and consequently, an increased urea-to-creatinine-level, due to physical barriers to self-hydration, a decrease in thirst sensation, use of diuretics and co-morbidity that increases water loss, including diabetes mellitus 21,25 . However, as we do not have measures of the (change in) body weight or alternative measures of hydration status, we cannot conclude to what extent dehydration caused the increased urea-to-creatinine-level in our population.…”
Section: Adj Hr (95% Ci) a P-valuementioning
confidence: 99%
See 2 more Smart Citations
“…We postulate that the urea-to-creatinine ratio might serve as a biomarker indicative of frailty. Elderly are more susceptible to dehydration and consequently, an increased urea-to-creatinine-level, due to physical barriers to self-hydration, a decrease in thirst sensation, use of diuretics and co-morbidity that increases water loss, including diabetes mellitus 21,25 . However, as we do not have measures of the (change in) body weight or alternative measures of hydration status, we cannot conclude to what extent dehydration caused the increased urea-to-creatinine-level in our population.…”
Section: Adj Hr (95% Ci) a P-valuementioning
confidence: 99%
“…Similar, Kirtane et al demonstrated that patients hospitalized with acute coronary syndrome and elevated serum urea levels were on average older, had a higher prevalence of co-morbidities and an increased short and long-term mortality rate 28 . In extension of these populations, an increased urea-to-creatinine ratio is also associated with worsening of renal function and all-cause mortality after hospitalization for acute heart failure 19,20 and long-term mortality among patients undergoing dialysis 21 . Thus, a higher urea-to-creatinine ratio might identify older, frail patients with an increased risk for long-term all-cause mortality after hospital discharge.…”
Section: Adj Hr (95% Ci) a P-valuementioning
confidence: 99%
See 1 more Smart Citation
“…Most studies that explored the relationship between renal-related biomarkers and mortality 7 15 had been conducted in special populations, such as persons with diabetes 2 , persons with CKD 7 , 9 , persons undergoing percutaneous intervention 8 , persons with hypertension 12 , or persons participating in comprehensive health screening programs 15 . By contrast, studies that focused on general populations are few 10 , 11 , 13 , 14 , 16 , 17 .…”
Section: Introductionmentioning
confidence: 99%
“…The results of investigations on renal-related biomarkers with mortality are inconsistent. Previous studies reported that high levels of blood urea nitrogen (BUN) are associated with an increase in all-cause mortality 7 9 . Low levels of eGFR reportedly have a positive 10 , 12 or a J-shaped association 11 or no association at all 9 , 13 with all-cause or CVD mortality.…”
Section: Introductionmentioning
confidence: 99%